2016
DOI: 10.1136/bmjopen-2015-010142
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy of selective serotonin reuptake inhibitors (SSRI) in treating major depressive disorder: a protocol for network meta-analysis of randomised controlled trials

Abstract: IntroductionThere have been inconsistent findings from randomised controlled trials (RCTs) and systematic reviews on the efficacies of selective serotonin reuptake inhibitors (SSRIs) as the first-line treatment of major depressive disorder (MDD). Besides inconsistencies among randomised controlled trials (RCTs), their risks of bias and evidence grading have seldom been evaluated in meta-analysis. This study aims to compare the efficacy of SSRIs by conducting a Bayesian network meta-analysis, which will be the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…A given drug is only effective in a fraction of the patients and its efficacy is variable (Jia et al 2016). We can use a system population model of 5HT signaling to study how a population of virtual individuals with a broad range of variation in all parameters responds to an SSRI treatment.…”
Section: Subpopulations With Special Properties Can Be Identifiedmentioning
confidence: 99%
“…A given drug is only effective in a fraction of the patients and its efficacy is variable (Jia et al 2016). We can use a system population model of 5HT signaling to study how a population of virtual individuals with a broad range of variation in all parameters responds to an SSRI treatment.…”
Section: Subpopulations With Special Properties Can Be Identifiedmentioning
confidence: 99%
“…In view of the pathways, a number of drugs are considered beneficial to combat depressive-like behavior. For instance, selective serotonin reuptake inhibitors (SSRIs), such as sertraline (Ser) and paroxetine, are the usual treatment options 4 . Nonetheless, long-term use of these drugs induces multiple inevitable side effects, including cognitive dysfunction, sexual dysfunction, dependence, weight gain, sedation and withdrawal 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, evidences also suggested that abnormal monoaminergic neurotransmission is one of most important mechanisms underlying depressive-like behavior. Numerous studies demonstrated that monoamines were important neurotransmitters involved in the etiology of depressive-like behavior 3 , 4 . Actually, most of the antidepressants act on more than one mechanisms, such as inhibition of the reuptake of serotonin (5-HT) and its metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…6. Hence the oxidant and antioxidant defence systems are getting deranged in depression 38 and diabetes 39 .…”
Section: Resultsmentioning
confidence: 99%